Proceedings of the International Conference on Modern Research in Aerospace Engineering MRAE-2016 (Lecture Notes in Mechanical Engineering,, 2018)
This book includes high-quality research papers presenting the latest advances in aerospace and related engineering fields. The papers are organized according to six broad areas (i) Aerospace Propulsion, (ii) Space Research, Avionics and Instrumentation, (iii) Aerodynamics Wind Tunnel and Computational fluid dynamics (CFD), (iv) Structural Analysis and Finite Element Method (FEM), (v) Materials, Manufacturing and Air Safety and (vi) Aircraft Environmental and Control System and Stability, making it easy for readers to find the information they require. Offering insights into the state of the art in aerospace engineering, the original research presented is valuable to academics, researchers, undergraduate and postgraduate students as well as professionals in industry and R&D. The clearly written book can be used for the validation of data, and the development of experimental and simulation techniques as well as other mathematical approaches. .